ANALISIS PENGARUH KEMAMPUAN DALAM MENGOPERASIKAN DAN MEMANFAATKAN TEKNOLOGI TERHADAP KINERJA KARYAWAN - Rhoma Iskandar; Nur Dwi Jayanto (Lembaga Pengembangan Kinerja Dosen, 2022)
The rapid development of technology is a challenge for every individual in the era of globalization. Technological developments affect almost all areas of life, one of which is the business world. Technological developments in the business world have both positive and negative impacts. The positive impact of technology in the business world is that it can increase productivity for the company. The rapid development of technology requires every individual to understand and have the skills to operate it in order to compete and survive in the world of work. The purpose of this study is to analyze the significance of the effect of skills/ability in operating and utilizing technology on the quality of employee performance. Data analysis in this study used descriptive qualitative methods, namely research methods carried out by collecting data from literature reviews. Data analysis using descriptive qualitative method shows that technology has a significant effect on company productivity. Thus a company needs employees who are capable and also skilled in operating modern technology. Based on this, being a workforce is important to understand and operate technology according to the company's needs. The ability to understand and operate technology greatly affects the performance of employees in particular and affects the productivity of the company in general.